Animal Models to Study Links between Cardiovascular Disease and Renal Failure and Their Relevance to Human Pathology - Hewitson, Tim D.; Holt, Stephen G.; Smith, Edward R. (Frontiers in Immunology, 2015)
The close association between cardiovascular pathology and renal dysfunction are well documented and significant. Patients with conventional risk factors for cardiovascular disease like diabetes and hypertension also suffer renal dysfunction. This is unsurprising if the kidney is simply regarded as a ‘modified blood vessel’ and thus traditional risk factors will affect both systems. Consistent with this, it is relatively easy to comprehend how patients with either sudden or gradual cardiac and or vascular compromise have changes in both renal haemodynamic and regulatory systems. However, patients with pure or primary renal dysfunction, also have metabolic changes (e.g. oxidant stress, inflammation, nitric oxide or endocrine changes) that affect the cardiovascular system. Thus cardiovascular and renal systems are intimately, bidirectionally and inextricably linked. Whilst we understand several of these links, some of the mechanisms for these connections remain incompletely explained. Animal models of cardiovascular and renal disease allow us to explore such mechanisms, and more importantly, potential therapeutic strategies. In this article we review various experimental models used, and examine critically how representative they are of the human condition